Important Factors in the Development of Biopharmaceutical Logistics Centers - Hyunjae Jung (Elsevier, 2021)
Human life is at the center of the fourth industrial revolution in the pharmaceutical trade. One of the major factors driving the growth of pharmaceuticals is the rapid growth of biopharmaceuticals. The global biopharmaceutical market is showing steady growth, and the current share of 20% of the drug market is expected to expand to 70% within the next 20 years. The domestic biopharmaceutical market has also turned into a trade surplus due to an increase of exports in 2017. Currently, there are no studies on the establishment of biopharmaceutical distribution centers. Therefore, in this study, it was assumed that the factors needed for the establishment of existing logistics centers and biopharmaceutical logistics centers would differ. In this study, three factors were extracted from a fuzzy AHP analysis – facility, location, and cost. In addition, 11 detailed factors were indicated, and their importance depended on temperature management devices, convenience of transportation, and the establishment of a logistics information system. Thus, facilities are more important in biopharmaceutical logistics centers than general logistics center.